Correlation of ABO and Rh Blood Group with Dental Malocclusion in Population of Mysuru - Paridhi Gupta; Bhagyalakshmi Avinash; Raghunath Nagasundara Rao (Wolters Kluwer Medknow Publications, 2020)
Introduction: Several studies have found that certain diseases are associated with ABO blood groups. The aim of the present study was to investigate the correlation of ABO Rh blood group with dental malocclusion in the population of Mysuru. Materials and Methods: In this study patients of 15-28 years of age will be selected, irrespective of gender from the hospital, Mysuru. It is an observational study with a duration of 3-4months. A total of 278 subjects between the age group of 15-28 years who visited the JSS hospital, Mysuru were recruited for this study. The maxillary and mandibular molar relation of teeth in maximum intercuspation using Angle's classification were recorded. Blood group was evaluated using the ABO blood grouping system. Mean, Standard deviation, frequency, percentage were used for descriptive statistics. Chi-square test was used for inferential statistics. Statistical Package of Social Science (SPSS), version 16 was used for statistical analysis. Results: Out of 278 people 'O' blood group was found to be most commonly associated with Angle's Class I malocclusion (71.3%). Class II div I and div II was found to be more common in 'A' blood group (42.68%) and (4.9%) respectively. Class III being most common in 'B' blood group (6.5%). Conclusions: A significant correlation exists between blood group and malocclusion. The prevalence of malocclusions being highest in blood group O, followed by A, B and AB in Mysuru. Class II div I malocclusion was more prevalent in 'A' followed by 'B' blood group.